Implementation of Smart Lock JT701 for Cargo Security System - Sundawa, Bakti Viyata; Batubara, Febrin Aulia; Nasution, Tuti Adi Tama; Darnila, Eva (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The freight forwarding business, namely transportation services from various modes of transportation (carrier) and arranging a series of shipments from several senders is growing rapidly during the pandemic and post Covid-19 pandemic. However, this business development is not without problems. Security disturbances during the cargo delivery process are a major problem, and this often happens in Indonesia. For this reason, this research will build a cargo delivery security system using automation technology and based on the Internet of Things (IoT). The system is a Smart Lock installed on the cargo. This smart lock can be monitored remotely, such as opening or closing the lock and the condition of the cargo in the field. Only the cargo owner can open or close the cargo lock. In addition, this system is also equipped with temperature and vibration sensors to maintain the quality of the goods in the cargo. The results of this research will be useful for the security system and convenience of the cargo delivery process and the digitization process will be easier to do in the future.